PENERAPAN KONSEP FREEDOM OF USE PADA KARYA ANNE LACATON DAN JEAN PHILIPPE VASSAL - Nurul Adha Sitorus; Masita Hanjayani; Hana Hali Nurrahmada; Iwan Sudrajat (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2026)
Abstract: Anne Lacaton and Jean Philippe Vassal are French architects renowned for their